Global Corruption Its Regulation under International Conventions, US, UK, and Canadian Law and Practice - Ferguson, Gerry (Open textbook library., 2022)
This book has been specifically created to make it easier for professors to offer a law school course on global corruption. It is also designed as a resource tool for all persons working in the anti-corruption field. The book is issued under a creative commons license and can be used for free in whole or in part for non-commercial purposes. The first chapter sets out the general context of global corruption: its nature and extent, and some views on its historical, social, economic and political dimensions. Each subsequent chapter sets out international standards and requirements in respect to combatting corruption – mainly in the UN Convention Against Corruption (UNCAC) and the OECD Bribery of Foreign Officials Convention (OECD Convention). The laws of the United States and United Kingdom are then set out as examples of how those Convention standards and requirements are met in two influential jurisdictions. Finally, the law of Canada is set out. Thus, a professor from Africa, Australia, New Zealand or English speaking countries in Asia and Europe has a nearly complete coursebook – for example, that professor can delete the Canadian sections of this book and insert the law and practices of his or her home country in their place. While primarily directed to a law school course on global corruption, this book will be of interest and use to professors teaching courses on corruption from other academic disciplines and to lawyers and other anti-corruption practitioners.